Empirical model of the main ionospheric trough for the nighttime winter conditions. (August 2016) - Karpachev, A.T.; Klimenko, M.V.; Klimenko, V.V.; Pustovalova, L.V.
Abstract: For the first time we developed an empirical model of the main ionospheric trough, MIT, for quiet (Kp=2) nighttime (18:00–06:00 LT) winter conditions in the Northern and Southern hemispheres for all levels of solar activity. The model consists of two parts: (1) the MIT position model in terms of geographical latitude and longitude; (2) the MIT shape model in terms of the latitudinal–longitudinal foF 2 variations in the range of 45–75 °N latitudes in the Northern hemisphere and of 40–80 °S in the Southern hemisphere. Thus, an empirical model of the quiet nighttime subauroral ionosphere has been developed. To construct this model the Interkosmos-19 and CHAMP satellites data have been used. The in-situ N e measurements at the CHAMP heights were transformed to the electron density at F 2 layer peak height (i.e. to N m F 2 and then to foF 2). In the frame of the model the diurnal and longitudinal variations in the MIT minimum position were revealed and studied in detail. Also the longitudinal and latitudinal variations in foF 2 in the MIT region were investigated. Accuracy of the model was tested according to the ground-based ionospheric stations data. It is shown that the constructed model much more adequately reproduces the variations in the winter nighttime subauroral ionospheric structure, including the MIT position and shape variations, than the International Reference Ionosphere model (IRI-2012). The online version of the MIT model is available on the IZMIRAN website:http://www.izmiran.ru/ionosphere/sm-mit/ for free using and more detailed testing. Highlights: Empirical model of the main ionospheric trough (MIT) for quiet nighttime winter conditions in the both hemispheres for all levels of solar activity was developed. The model consists of two parts: MIT position model in terms of geographical latitude and MIT shape model in terms of the foF 2 maps. Interkosmos-19 and CHAMP data were used. The model is available on:www.izmiran.ru/ionosphere/sm-mit/ .